Ragam Teknik Interpretasi Dan Pemahaman Dalam Fiqh Al-Hadis Serta Contoh Aplikatifnya - Muhammad Sabir; Andi Mujahidil Ilman; Muhammad Alwi Nasir; Nur Muthmainnah (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2023)
The existence of the hadith of the Prophet As a reference guide for the second law after the Qur’an, it is very necessary to explain the essence of Divine Words. Hadith studies are basically not only oriented in the scope of quality studies but also in aspects of their content. Understanding hadith requires a variety of technical approaches to obtain complex meaning, such as textual interpretation (language patterns), intertextual (comparison with other narrations that are tanawwu’ and with the Qur’an) and contextual (the process of tracing common threads and then connecting them with current conditions). . Like the hadith regarding the prohibition of sitting in the hibwah position (sitting hugging the knees) while listening to Friday sermons. The prohibition on this hadith is not qat’i, but for reasons related to the sitting position, namely because it can cause open genitals and a feeling of drowsiness when listening to the sermon. So contextually it can be concluded, all kinds of sitting that can make the genitals open and cause drowsiness are prohibited.